SDG 14 Exploiting and Managing the Alien and Unseen World below Water - Holm, Poul (Oxford University Press, 2022)
The problem with the ocean is that we do not see what is below the surface. When we clear land for urban development, when we change agricultural practices, when we cut the trees or kill off the wolves, we see the changes. The environmental history of the land is well documented, and archaeologists and historians have long been able to record and visualize past landscapes. What happens below the sea surface was largely hidden to the human eye until the development of scuba diving and submarine photography in the second half of the twentieth century.
Before the UN Sustainable Development Goals.
PUBLISHED
Oxford
Keywords: Smart & Sustainable Planet; environmental history